Cytokines, thyroid autoantibody synthesis and thyroid cell survival in culture. - McLachlan, S M (1990)
In autoimmune thyroid disease lymphoid cells infiltrating the thyroid gland occur in conspicuous aggregates or as a diffusely distributed population invading the thyroid follicles. Consequently cytokines secreted by activated T cells or macrophages could influence neighbouring thyroid cells as well as other lymphocytes. We have investigated this possibility using recombinant cytokines. Thyroid cell survival was assessed in terms of mitochondrial dehydrogenase activity in monolayers exposed to tumour necrosis factor-alpha (TNF-alpha), interferon-gamma (IFN-gamma), interleukin-1 (IL-1 alpha and beta) and interleukin-2 (IL-2) in the presence or absence of thyroid-stimulating hormone (TSH). Neither TNF-alpha nor IL-2 affected thyroid cell survival, IFN-gamma was usually inhibitory and IL-1 alpha slightly enhanced cell survival in some experiments. However, the effects were small and variable and were not enhanced by potentially synergistic combinations of cytokines, longer periods of exposure, or different culture conditions. In contrast, IFN-gamma, IL-2 and TNF-alpha inhibited the ability of thyroid lymphocytes from patients with Graves' disease and Hashimoto's thyroiditis to synthesize autoantibodies to thyroid peroxidase (TPO) and thyroglobulin (Tg). Comparison of lymphoid populations isolated by digestion and/or mechanical disaggregation indicated that a population of activated B cells, plasma cells and T cells, intimately associated with thyroid cells since they could only be extracted by digestion, was influenced by cytokines. Our studies suggest that in addition to its well-recognized ability to induce MHC class II antigens on thyroid cells, IFN-gamma may inhibit thyroid cell proliferation and TNF-alpha, IFN-gamma and IL-2 may down-regulate thyroid autoantibody synthesis.